Pleurotus spp. cultivation on Brachiaria sp. straw treatment with alkaline water: Oyster mushroom and substrate treatment - Iossi, Matheus Rodrigo [UNESP]; Cobos, Juan Diego Valenzuela; Alegria, Francisco J. Gea; Zied, Diego Cunha [UNESP] (Springer Nature, 2018)
The aim of this research was to evaluate the efficiency of aqueous alkali-treated Brachiaria straw for the cultivation of appropriate species of oyster mushroom. The substrate used in the cultivation of various Pleurotus spp. was soaked for 20 min by using two different procedures: (i) 0.5–2.0% Ca(OH)2 in 100 L water, and (ii) 50–250 L water. As a result, 1% Ca(OH)2 dissolved in 100 L water and 3.5 kg of Brachiaria straw presented the best production. The most suitable species for the application of the present method were P. pulmonarius and P. sapidus. The success of this technique is directly related to the concentration of Ca(OH)2 and water, the species, and the origin and quality of raw material used as the substrate in the production of oyster mushroom.
Keywords: Brachiaria straw; Cheap treatment; Sciarid flies; Yield